Weaker HLA footprints on HIV in the unique and highly genetically admixed host population of Mexico - Soto-Nava, Maribel; Avila-Ríos, Santiago; Valenzuela-Ponce, Humberto; García-Morales, Claudia; Carlson, Jonathan M.; Tapia-Trejo, Daniela; Garrido-Rodriguez, Daniela; Alva-Hernández, Selma N.; García-Tellez, Thalía A.; Murakami-Ogasawara, Akio; Collaborative, the International HIV Adaptation; Mallal, Simon A; et al. (Journal of Virology, 2017)
HIV circumvents HLA class I-restricted CD8+ T cell responses through selection of escape mutations that leave characteristic mutational "footprints" - also known as HLA-associated polymorphisms (HAPs) - on HIV sequences at the population level. While many HLA footprints are universal across HIV subtypes and human populations, others can be region-specific as a result of the unique immunogenetic background of each host population. Using a published probabilistic phylogenetically-informed model, we compared HAPs in HIV Gag and Pol (PR-RT) in 1,612 subtype B-infected, antiretroviral treatment-naïve individuals from Mexico and 1,641 from Canada/USA. A total of 252 HLA class I allele subtypes were represented, including 140 observed in both cohorts, 67 unique to Mexico and 45 unique to Canada/USA. At the predefined statistical threshold of q<0.2, 358 HAPs (201 in Gag; 157 in PR-RT) were identified in Mexico, while 905 (534 in Gag and 371 in PR-RT) were identified in Canada/USA. HAP identified in Mexico included both "canonical" HLA-associated escape pathways and novel associations, in particular with HLA alleles enriched in Amerindian and mestizo populations. Remarkably, HLA footprints on HIV in Mexico were not only fewer but also on average significantly weaker than those in Canada/USA, though some exceptions were noted. Moreover, exploratory analyses suggested that the weaker HLA footprint on HIV in Mexico may be due, at least in part, to weaker and/or less reproducible HLA-mediated immune pressures on HIV in this population. The implications of these differences for natural and vaccine-induced anti-HIV immunity merit further investigation. IMPORTANCE HLA footprints on HIV identify viral regions under intense and consistent pressure by HLA-restricted immune responses and the common mutational pathways that HIV uses to evade them. In particular, HLA footprints can identify novel immunogenic regions and/or epitopes targeted by understudied HLA alleles; moreover, comparative analyses across immunogenetically distinct populations can illuminate the extent to which HIV immunogenic regions and escape pathways are shared versus population-specific, information which can in turn inform the design of universal or geographically-tailored HIV vaccines. We compared HLA-associated footprints on HIV in two immunogenetically distinct North American populations - Mexico and Canada/USA. We identify both shared and population-specific pathways of HIV adaptation, but also make the surprising observation that HLA footprints on HIV in Mexico are overall fewer and weaker than in Canada/USA, raising the possibility that HLA-restricted antiviral immune responses in Mexico may be weaker, and/or escape pathways somewhat less consistent, than in other populations.